Empire : the Rise and demise of the British world order and the lessons for global power - Ferguson, Niall (Basic Books, 2008)
A splendid history ... If Americans want to be convinced of the benefits of empire, as well as apprised of its costs, they need merely pick up Ferguson's dazzling book.- Weekly Standard.